ANTESEDEN CUSTOMER VALUE DAN MINAT BELI ULANG PADA TOKO BATIK LASEM SUMBER LANGGENG - Hidayati, Novia; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
This research is based on to the higher community awareness of local resources. Batik lasem is one of local in Rembang area. The purpose of this study is to analyze the effect of image of origin product (X1), perception price (X2), and the attractiveness of the product (X3) on customer value (Y1) and the implications for repeated purchase of Â â€œBatik Lasem Sumber Langgengâ€. This research use 5 variables, 16 indicators, andÂ  4 hypothesis and by testing using 385 respondents. Analysis techniques the data used was structural equation model ( SEM ) of the amos 20.0. The data is the primary and uses a questionnaire with open and closed questions.The result of this research prove 4 hypothesis advanced by accepted and significant. The research show image of origin product, perception price and the attractiveness of the product significant positively affect to customer value and customer value significant positively affect to repeated purchase. In addition to thatÂ  sobelÂ  test of the research indicated that the variable intervening also proved.